2020
DOI: 10.14639/0392-100x-n0618
|View full text |Cite
|
Sign up to set email alerts
|

Results of a survey on elderly head and neck cancer patients on behalf of the Italian Association of Radiotherapy and Clinical Oncology (AIRO)

Abstract: A, et al. Results of a survey on elderly head and neck cancer patients on behalf of the Italian Association of Radiotherapy and Clinical Oncology (AIRO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…An online survey asking radiation oncologists with expertise in HNSCC identified a gap in the management of older adult HNSCC patients. Only 10% of the radiation oncologists interviewed performed a CGA in older adult patients and approximately 7% of multidisciplinary tumor boards included a geriatrician [ 27 ]. This is problematic as another study found that for approximately 60% of cancer cases discussed with a multidisciplinary team, the diagnosis and management of the patient changed [ 28 ].…”
Section: Geriatric Assessmentsmentioning
confidence: 99%
“…An online survey asking radiation oncologists with expertise in HNSCC identified a gap in the management of older adult HNSCC patients. Only 10% of the radiation oncologists interviewed performed a CGA in older adult patients and approximately 7% of multidisciplinary tumor boards included a geriatrician [ 27 ]. This is problematic as another study found that for approximately 60% of cancer cases discussed with a multidisciplinary team, the diagnosis and management of the patient changed [ 28 ].…”
Section: Geriatric Assessmentsmentioning
confidence: 99%
“…Previous studies have reported that 16.7-38.7% of patients underwent a change in treatment following the geriatric assessment. [41][42][43][44][45][46] An Italian survey by AIRO on elderly HNSCC patients showed that while the majority of cases were discussed in a multidisciplinary setting, a geriatrician was rarely part of the clinic, and comprehensive geriatric assessment was performed in only 10% of radiotherapy-oncology departments, thus risking under or overtreatment due to inaccurate frailty assessments 47 . There is still the need for larger, more HNSCC-focused study that may be used in the future as the basis for risk strati cation and decision making, as there is now available only limited evidence to support default geriatric assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey study published in 2020, only 10% of the HNSCC radiation oncologists in Italy stated that they performed a CGA in older adult patients. 60 …”
Section: Work-upmentioning
confidence: 99%
“…In a survey study published in 2020, only 10% of the HNSCC radiation oncologists in Italy stated that they performed a CGA in older adult patients. 60 In addition to geriatric assessments, there are several predictive models to calculate probabilities of cancer-related events. The Generalized Competing Event (GCE) model is a way of risk-stratifying patients by weighing the relative hazard of cancer-and non-cancer-related events.…”
Section: Geriatric Assessmentsmentioning
confidence: 99%